2017
DOI: 10.5530/ijper.51.4s.105
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid and Sensitive Bio Analytical RP-HPLC Method for Detection of Docetaxel: Development and Validation

Abstract: Objective: A rapid and selective high-performance liquid chromatographic (HPLC) method has been developed and validated for Docetaxel anhydrous (DTX) using Ketoconanzole (KCZ) as an internal standard in biological fluids. Methods: The analyte was extracted from human plasma by liquid-liquid extraction method using acetonitrile. The analysis was carried out on Licrosphere IV, C 8 column (LC-GC Chromatography Solutions Pvt. Ltd, Mumbai, and India) (4.6×250 mm) with isocratic elution using a mobile phase composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…Several previous reports claim to develop a rapid, sensitive, and reliable HPLC method for the detection of docetaxel (DTX) in biological matrices [36,37]. Attempts have also been made to develop and validate methods to detect DTX-loaded PLGA nanoparticles [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous reports claim to develop a rapid, sensitive, and reliable HPLC method for the detection of docetaxel (DTX) in biological matrices [36,37]. Attempts have also been made to develop and validate methods to detect DTX-loaded PLGA nanoparticles [38].…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative determination of analytes and drug metabolites in the biological matrix plays an important role in the estimation and interpretation of bioavailability, bioequivalence, and pharmacological and pharmacokinetic profiles of a drug [36]. Data suggested that the specificity, accuracy, and precision followed ICH guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…It was analyzed as the ratio of the peak area of extracted plasma samples as per sample preparation in three replicates to unextracted plasma-free samples in three replicates [23]. It was, analyzed by plasma concentrations of tulobuterol hydrochloride such as 150, 300, and 450 ng/ml at 50, 100, and 150 %.…”
Section: Recoverymentioning
confidence: 99%
“…Since being approved for use in chemotherapy by the Food and Drug Administration (FDA) in 1996, researchers have developed numerous analytical methods to monitor DOC in various animal and human matrices, including blood and its fractions, saliva, urine, and feces [1]. While the majority of procedures for the analysis of DOC developed since 2010 have been based on liquid chromatography (LC) [12][13][14][15][16][17][18][19] and ultra-performance liquid chromatography (UPLC) [20], methods based on capillary electrophoresis (CE) [21] and immunoassays have also been reported [22]. In these works, the complex biological matrices containing DOC are subjected to sample preparation prior to instrumental analysis, mainly via classical extraction techniques such as liquid-liquid extraction (LLE) [12,13,19], protein precipitation (PPt) [14,15,23] and solid-phase extraction (SPE) [16][17][18]; however, to the best of our knowledge, microextraction techniques have yet to be applied to isolate DOC from biological matrices.…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of procedures for the analysis of DOC developed since 2010 have been based on liquid chromatography (LC) [12][13][14][15][16][17][18][19] and ultra-performance liquid chromatography (UPLC) [20], methods based on capillary electrophoresis (CE) [21] and immunoassays have also been reported [22]. In these works, the complex biological matrices containing DOC are subjected to sample preparation prior to instrumental analysis, mainly via classical extraction techniques such as liquid-liquid extraction (LLE) [12,13,19], protein precipitation (PPt) [14,15,23] and solid-phase extraction (SPE) [16][17][18]; however, to the best of our knowledge, microextraction techniques have yet to be applied to isolate DOC from biological matrices. This gap in the literature is notable, as microextraction techniques use significantly less hazardous chemicals, thus aligning them with the principles of green chemistry.…”
Section: Introductionmentioning
confidence: 99%